End of life decisions in Malaysia: adequacies of ethical codes and developing legal standards - Jahn Kassim, Puteri Nemie; Alias, Fadhlina (2014)
End of life decisions constitute one of the areas in medical practice in which ethical dilemmas and legal interventions have become increasingly prevalent. As continuous technological and pharmacological advances prolong life expectancy of those suffering from terminal illnesses, the medical profession is constantly confronted with difficult decisions on whether to forego or limit care. Such decisions are presently no longer confined to mere clinical assessments but involve wider considerations such as patient’s religious and cultural beliefs, financial constraints, wishes and needs of family members, healthcare providers and members of the community. Therefore, it is imperative that ethical codes and legal standards are developed comprehensively to provide guidance for the medical profession in deciding on the best possible actions for such patients. Medical decisions that are in congruent with the highest ethical values and adhering to legal standards will inevitably solve the inherent ethical dilemmas that are very pronounced in this area. Although there are available Malaysian ethical codes and relevant legal provisions governing some aspects of end of life decisions, but the development of the law and ethical codes have yet to reach its fullest extent. Similarly, end of life decisions are still within the unchartered judicial terrain in Malaysia and the use of advance directives in planning end of life decisions appears to be a novel concept amongst patients in Malaysia. Thus, the development of comprehensive ethical codes in tandem with developing legal standards is considered a significant necessity for Malaysia in order to promote a holistic decision making in end of life issues.